Exploiting the elastic properties of metallic glass thin foils: the undulatory mechanical response upon loading under geometric confinement - Shahin Elzoubi, Osama (Cranfield University, 2023)
A peculiar mechanical response was recently observed for metallic glass thin foils in confined geometries under normal loading. In particular, when an arc-shaped metallic glass foil is subjected to normal loading, it deforms elastically, changing its shape by progressively increasing the number of formed sinusoidal arcs. This mechanical response type is called undulatory behaviour and results from a combination of successive elastic bending and buckling events occurring on the foil. This behaviour is reversible and repeatable as long as the deformation of metallic glass foils remains within the elastic deformation limit for metallic glasses (< 2% strain) and can be exploited for developing novel types of nonlinear springs. The undulatory behaviour of metallic glasses was first reported in 2016 and has been very little studied. This project aims to explore the limitations of studying the mechanism and the underlying phenomena associated with this behaviour and exploit its potential for engineering applications. More specifically, the undulatory behaviour for three different metallic glass systems (i.e. Fe-Cr-Si-B and Ni-Fe-Si- B-Mo and Ni-B-Si) with varying thicknesses of foil in the range from 19 – 40 μm was studied, and various initial set-up geometries were investigated. Specific focus was given to understanding the mechanism of the undulatory behaviour, establishing some spring design principles and exploring the cycling fatigue life of the glassy foils. The undulatory behaviour involves elastic deformation, buckling and post- buckling phenomena occurring in a repeatable sequence. Buckling plays a significant role in the mechanism of undulatory behaviour. The required load for buckling was approached using the Euler’s for buckling. The standing wave was shown to be able to describe the sequence of the undulatory response but only for the waveforms with perfect sinusoidal arcs. The parameters of the initial arc’s geometry set-up, such as the boundary length (chord), amplitude, and foil thickness enable the tuning of the undulatory behaviour and offer capabilities for designing spring-type devices with desirable characteristics that can efficiently operate in different load ranges. Under cyclic loading the glassy foils endured between 19 x 10³to 225 x 10³ cycles, depending on load/strain parameters, foil thickness and alloy compositions, typically higher than conventional low cycle springs. Crack initiation during cyclic loading was found to be associated with surface defects and side edges of the foils. This unique mechanical response of metallic glass foils makes them a promising material for a wide range of applications, contributing to being exploited for the enormous potential for designing novel types of micro-flat springs using the exceptional mechanical and elastic properties of metallic glass foils.
Salonitis, Konstantinos - Associate Supervisor Panagiotopoulos, Nikalaos - Associate External Supervisor
Keywords: metallic glass foils; undulatory behaviour; buckling; flat micro-springs; cycling fatigue life; elastic deformation